The Mediating Role of Change Management Between Technology Readiness and Job Performance - Hamad, Samer (European Scientific Journal, ESJ, 2025)
This research investigates the interaction between technology readiness, change management, and job performance. The effects of technology readiness on change management and job performance, while on the other hand, the mediation impact of change management on job performance has been explored. A self-report questionnaire was distributed to obtain a representative sample, yielding 409 complete responses. All questions were mandatory to prevent missing data. The survey began with demographic items (age, gender, education, years spent in the organization tenure, and work experience), followed by validated scales: Technology readiness (optimism and innovativeness), Change management (leadership support and participation/communication), Job performance (perceived organizational support and work-life conflict). A Structural Equation Modeling (SEM) approach was selected for its unique advantages in testing complex theoretical relationships. Despite excellent model fit (CFI=0.98, RMSEA=0.03), the results revealed theoretically significant null findings: technology readiness showed no significant direct effect on change management (β=0.12, p=.08) or job performance (β=0.09, p=.15), and change management did not mediate job performance (β=0.14, p=.11). These results suggest that the widely accepted link between technology readiness and change management desire may be more context-dependent than previous research indicates. While models like the Technology Acceptance Model (TAM) and Unified Theory of Acceptance and Use of Technology (UTAUT) posit direct relationships between these constructs, the findings imply that in organizational settings where change is mandated rather than voluntary, individual readiness may become less influential. These insights suggest organizations should focus more on structural implementation factors than individual preparation when mandating technological changes, offering a new perspective for both research and practice in organizational change management.